Evaluation of a blended E-Service-Learning Subject on Service Leadership during the COVID-19 pandemic. - Ho, Wynants; Shek, Daniel T. L.; Chan, Cathy H. M. (International Journal of Child Health & Human Development, 2024)
The purpose of this study was to investigate the effectiveness and students' perceptions of a blended service-learning subject on service leadership during the COVID-19 pandemic in Hong Kong. A one-group pretest and posttest comparison (n = 39) was conducted to assess changes in students' positive youth development attributes, life satisfaction, and leadership qualities after completing the course. Additionally, a post-lecture questionnaire (n = 64) was administered to gather insights into students' perspectives in the blended service leadership subject. Results indicated that the blended service leadership subject significantly improved students' life satisfaction and character strengths, and students held positive perceptions of course design and perceived benefits, the performance of the lecturer, and the overall blended learning experience. The findings of this study added to our understanding of the effectiveness and the application of blended e-servicelearning in enhancing students' well-being and leadership skills, it also provided insights from students' perspectives of using the blended learning mode in leadership education.